Hysteria and Gender Culture: A Study of Catherine in Wuthering Heights - Hung-Chang Liao; Ya-huei Wang (ELLITE, 2022)
Since ancient times, hysteria has been recognized as a woman's uterine lesion or a disease related to the possession of evil spirits. However, modern social studies have re-examined the symptoms of hysteria and determined that what has been termed “hysteria” can actually be connected to psychological symptoms related to a woman’s failure to obey the prescribed social gender norms or adhere to societal gender images. Hence, hysteria may be a subconscious or unconscious, though always ineffective, attempt to fight against oppressive gender expectations. In order to escape the pressure from prescribed gender norms or patriarchal norms, women may retreat into a world of insanity, using hysteria to release their anger or anxiety. In order to further illustrate how hysteria fights against the existing cultural structure, this study uses Wuthering Heights as an example of hysteria as a consequence of the perspectives of gender, family structures, and social class, as well as the interactive effects of these dimensions. To achieve this goal, the study applies the theories and criticisms of gender psychology, gender criticism, and binary gender opposition to analyze the symptoms of female hysteria in literature and to demonstrate how women, forced to conform to prescribed gender images, use hysteria as a defense mechanism to express their anger toward gender subjectivity; it also aims to further deconstruct the androcentric society and discourses based on gender binary opposition.